Mentha X Piperita, Ocimum basilicum e Salvia deserta, (Lamiaceae): abordagens fisiológicas e fitoquímicas - Búfalo, Jennifer [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Medicinal and aromatic plants such as peppermint (Mentha x piperita), sweet basil (Ocimum basilicum) and salvia (Salvia deserta) have great importance in the global context due to the demand of the food, chemical, and pharmaceutical industries. Peppermint is used by folk medicine and is grown mainly for essential oil extraction. The study investigated whether osmotic stress induced by two polyethyleneglycol (PEG) levels, in a short time, in peppermint changes the physiological pattern, anatomy, leaf ultrastructure and essential oil content and composition. The results indicated that osmotic stress responses were dose dependent, as plants subjected to PEG 50 g L-1 maintained structural features and metabolic functions similar to those of control plants. Plants exposed to PEG 100 g L-1 showed anatomical changes and ultrastructural damage as degradation and organelles lysis, which are in agreement with the low leaf water potential, gas exchange reduction, increase of total sugars, and activity of antioxidant enzymes. These plants showed lower content and quality of essential oil. Sweet basil, an important medicinal plant used mainly in culinary arts, was grown in a greenhouse using both organic and conventional fertilization systems with two nitrogen rates each (150 and 250 kg N/ha). The results showed that the highest fresh weight was obtained from the plants grown with conventional fertilizer at a rate of 250 kg N/ha. The treatments did not affect the essential oil content, yield, and composition and linalool was the major compound found in the study. The results showed that regardless of fertilizer, organic or conventional, there was no change in the composition of the oil. The bioprospecting conducted with S. deserta roots identified the presence of four diterpenes with biological activities. Taxodione showed leishmanicidal, antifungal, and antimicrobial activity, and the ferruginol displayed the greatest activity (24-h IC50 1.29 mg/L) ...
Mentha X Piperita, Ocimum basilicum e Salvia deserta (Lamiaceae): phytochemical and physiological approaches
Keywords: Hortelã; Manjericão; Diterpenos; Essências e óleos essenciais; Plantas aromaticas; Plantas medicinais; Medicinal plants; Basil; Spearmint